COMMERCIALLY PRODUCED STUFF FOR ADDITIONAL FEEDING IN INFANTS’ NUTRITION - I.Ya. Kon’; A.I. Safronova (Вопросы современной педиатрии, 2010)
The article describes a problem of rational nutrition of infants with commercially produced additional feeding stuff containing fruits and vegetables. Equally with traditional form of fruits and vegetables in infants’ nutrition (juices, nectars, mashed products), there are new types of food — combined mush products containing fruits, cereals and milk. The article analyzes compound, properties of these products and peculiarities of their use in infants’ nutrition. Authors give recommendations on terms of inclusion these products in diet of infants.Key words: infants, nutrition, additional feeding, mashed products.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):119-123)